Math Online: Student’s Perspective Based on Survey - Stankous, Nina; Buibas, Martha (European Scientific Journal, ESJ, 2018)
In online education, technology replaces some or all face-to-face interactions as self-paced content is delivered online. The assessment of technology in education is challenging because measuring learning is difficult and, it is hard and sometimes impossible to attribute learning to any one element, due to many confounding factors. In our paper, we discuss results of a student’s survey related to online math courses and technology. In our previous research, we discussed the benefits and challenges of online education from the point of view of teaching methods. Now we want to gauge and analyze what students think about their math online classes. We are asking students whether they prefer the online or onsite formats for math classes—or whether it matters at all. We also ask if learning math in online classes is more difficult than online courses in other subjects; and why students like the online format (convenience, time savings, working on your own schedule, more independent thinking, etc.) They can also add some other reasons. We discuss with our students what makes online math classes more challenging then onsite classes, including lack of communication, time delays in answering your questions, lack of interaction with classmates, high level of computer literacy and technical problems. One of the questions we examine is the usage of external resources like YouTube or Khan Academy. Also, students share and discuss some other websites and software they utilize as additional assistance tools for their math online classes. Best practices and recommendations will be given based on our own experience and survey, along with results of other research.